Kesenjangan Profil Antara Hard Skills dan Soft Skills Lulusan SMK Jurusan Rekayasa Perangkat Lunak dengan Kebutuhan Industri Bidang Teknologi Informasi di Kota Malang - Dayu Ikhwanika Prasetyo; Admaja Dwi Herlambang; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
This research was conducted to determine the expectations of the information technology industry as well as the reality of the ability of hard skills and soft skills held by vocational graduates of software engineering, see the gap between expectations and the reality of the ability of hardskills and soft skills graduates and to know the competencies prioritized and need attention in improving the quality of education in vocational schools . This study uses an evaluation research type, with a quantitative approach supported by a qualitative approach and for discrepancies using a discrepancy evaluation model, for the research design used ex post facto design, sampling techniques using purposive sampling, the number of respondents involved is 10 companies, data is collected with interviews and questionnaires. The results showed that there were company expectations of the competencies possessed by vocational school graduates and the reality in the field, graduates had not met industry expectations. Then there is a gap between expectations and reality in the field of graduates' soft skills. With natural science analysis, leadership abilities are highly prioritized and abilities. discipline, critical thinking, creative thinking, database competencies and Mobile Programming Web Programming need to be re-examined by schools.